Thermoelectric conversion element and thermoelectric conversion module
By using CuZn alloy electrodes and intermediate layers of different compositions in the thermoelectric conversion element, the bonding between the MgSbBiTe system thermoelectric conversion material and the electrode is improved, the problem of high resistance is solved, and the performance of the thermoelectric conversion module is improved.
Patent Information
- Application Number
- CN201880004572.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-06-27
- Filing Date
- 2018-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2038-11-12
AI Technical Summary
In existing thermoelectric conversion components, the bonding of electrodes and thermoelectric conversion materials is low, resulting in a high resistance, which limits the performance of the thermoelectric conversion module.
The first electrode and the second electrode composed of CuZn alloy are used, and different intermediate layers are provided between the thermoelectric conversion layer and the electrode to improve the bonding property between the MgSbBiTe-based thermoelectric conversion material and the electrode.
By improving the bonding of the thermoelectric conversion material and the electrode, the resistance of the thermoelectric conversion element is significantly reduced, thereby improving the performance of the thermoelectric conversion module.
Smart Images

Figure CN110998882B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a thermoelectric conversion element and a thermoelectric conversion module. Background Art
[0002] A thermoelectric conversion element composed of a thermoelectric conversion material and a pair of electrodes joined to the thermoelectric conversion material is known. An n-type thermoelectric conversion element can be constructed by an n-type thermoelectric conversion material. A p-type thermoelectric conversion element can be constructed by a p-type thermoelectric conversion material. A thermoelectric conversion module composed of a combination of an n-type thermoelectric conversion element and a p-type thermoelectric conversion element can generate electricity based on a temperature difference generated by the inflow of thermal energy.
[0003] Non-Patent Document 1 discloses a thermoelectric conversion element composed of a MgAgSb-based thermoelectric conversion material and a pair of Ag electrodes bonded to the material.
[0004] Patent Document 1 discloses a MgSbBiTe-based thermoelectric conversion material.
[0005] Prior Art Literature
[0006] Patent Document 1: Japanese Patent No. 6127281
[0007] Non-patent document 1: D. Kraemer et.al., "High thermoelectric conversion efficiency of MgAgSb-based material with hot-pressed contacts", Energy Environ. Sci., 2015, 8, 1299-1308 Summary of the invention
[0008] As the resistance between a pair of electrodes in a thermoelectric conversion element decreases, the thermoelectric conversion performance of a thermoelectric conversion module including the element improves.
[0009] The present disclosure provides a new technology capable of more reliably reducing the resistance of a thermoelectric conversion element using a MgSbBiTe-based thermoelectric conversion material.
[0010] The present disclosure provides the following thermoelectric conversion element.
[0011] A thermoelectric conversion element comprises a first electrode, a second electrode, a first intermediate layer, a second intermediate layer and a thermoelectric conversion layer.
[0012] The first intermediate layer is provided between the thermoelectric conversion layer and the first electrode.
[0013] The first intermediate layer is in contact with the thermoelectric conversion layer,
[0014] The first electrode is in contact with the first intermediate layer,
[0015] The second intermediate layer is provided between the thermoelectric conversion layer and the second electrode.
[0016] The second intermediate layer is in contact with the thermoelectric conversion layer,
[0017] The second electrode is in contact with the second intermediate layer,
[0018] The first electrode and the second electrode are made of CuZn alloy.
[0019] The thermoelectric conversion layer is composed of a thermoelectric conversion material containing Mg.
[0020] The thermoelectric conversion material contains at least one element selected from Sb and Bi,
[0021] The thermoelectric conversion material contains at least one element selected from Se and Te,
[0022] The thermoelectric conversion material has La 2 O 3 The crystal structure of
[0023] The composition of the first intermediate layer is different from the composition of the first electrode and the composition of the thermoelectric conversion layer.
[0024] The composition of the second intermediate layer is different from the composition of the second electrode and the composition of the thermoelectric conversion layer.
[0025] According to the present disclosure, the resistance of a thermoelectric conversion element using a MgSbBiTe-based thermoelectric conversion material can be reduced more reliably. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram showing an example of the thermoelectric conversion element of the present disclosure.
[0027] Figure 2 It is a schematic diagram showing an example of the thermoelectric conversion module of the present disclosure.
[0028] Figure 3 This is a diagram showing an X-ray diffraction pattern of the thermoelectric conversion material prepared in Example 1.
[0029] Figure 4 This is a diagram showing an energy dispersive X-ray analysis (hereinafter referred to as “EDX”) spectrum of the thermoelectric conversion material produced in Example 1.
[0030] Figure 5AThis is an image of a cross section of the thermoelectric conversion element produced in Example 1 observed using a scanning electron microscope (hereinafter referred to as “SEM”).
[0031] Figure 5B It means that through EDX Figure 5A Figure 1 is a graph showing the results of a ray analysis of the section shown.
[0032] Fig. 6A This is an image of a cross section of the thermoelectric conversion element produced in Example 2 observed using a SEM.
[0033] Figure 6B It means that through EDX Fig. 6A Figure 1 is a graph showing the results of a ray analysis of the section shown.
[0034] Fig. 7A This is an image of a cross section of the thermoelectric conversion element produced in Comparative Example 1 observed using a SEM.
[0035] Figure 7B It means that through EDX Fig. 7A Figure 1 is a graph showing the results of a ray analysis of the section shown.
[0036] Description of Reference Numerals
[0037] 1 (n-type) thermoelectric conversion element
[0038] 2 Thermoelectric conversion layer
[0039] 3. Middle Layer
[0040] 3a 1st intermediate layer
[0041] 3b Second intermediate layer
[0042] 4 Electrodes
[0043] 4a 1st electrode
[0044] 4b Second electrode
[0045] 5a Page 1
[0046] 5b Side 2
[0047] 11 Thermoelectric conversion module
[0048] 12a, 12b, 12c, 12d Bonding material layer
[0049] 13a 1st external electrode
[0050] 13b Second external electrode
[0051] 13c Third external electrode
[0052] 21 p-type thermoelectric conversion element
[0053] 22 p-type thermoelectric conversion unit
[0054] 23a The third electrode
[0055] 23b 4th electrode
[0056] 24a Page 3
[0057] 24b Page 4
[0058] 51 Thermoelectric conversion layer
[0059] 52 Metamorphic layer
[0060] 53 Ni layer DETAILED DESCRIPTION
[0061] (Incorporated by reference)
[0062] In this application, Japanese Patent Publication No. 6127281 and the corresponding U.S. Patent Publication No. 2017 / 0117453 are referenced and cited.
[0063] (Insights that form the basis of this disclosure)
[0064] According to the research of the present inventors, the bonding property between the MgSbBiTe-based thermoelectric conversion material and the electrode is greatly affected by the Mg contained in the material. More specifically, in the MgSbBiTe-based thermoelectric conversion material, the high diffusivity of the Mg contained in the material will lead to reduced bonding with the electrode. In the MgAgSb-based thermoelectric conversion material disclosed in non-patent document 1, there is no report on the effect of Mg on the bonding property with the electrode. According to further research by the present inventors, the bonding property between the MgSbBiTe-based thermoelectric conversion material and the electrode is improved by using the first electrode and the second electrode, and the first intermediate layer and the second intermediate layer composed of CuZn alloy. Through the improvement of this bonding property, the resistance of the thermoelectric conversion element using the MgSbBiTe-based thermoelectric conversion material can be more effectively reduced.
[0065] (Embodiments of the present disclosure)
[0066] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0067] [Thermoelectric conversion element]
[0068] An example of the thermoelectric conversion element disclosed in the present invention is shown in Figure 1 . Figure 1The thermoelectric conversion element 1 includes a thermoelectric conversion layer 2, a first intermediate layer 3a, a second intermediate layer 3b, a first electrode 4a, and a second electrode 4b. The thermoelectric conversion layer 2 has a first surface 5a and a second surface 5b. The second surface 5b is a surface on the opposite side of the first surface 5a. The first intermediate layer 3a is arranged between the thermoelectric conversion layer 2 and the first electrode 4a. The first intermediate layer 3a is in contact with the thermoelectric conversion layer 2. The first electrode 4a is in contact with the first intermediate layer 3a. The second intermediate layer 3b is arranged between the thermoelectric conversion layer 2 and the second electrode 4b. The second intermediate layer 3b is in contact with the thermoelectric conversion layer 2. The second electrode 4b is in contact with the second intermediate layer 3b.
[0069] exist Figure 1 In the element 1, the shape of the thermoelectric conversion layer 2 is a rectangular parallelepiped. However, the shape of the thermoelectric conversion layer 2 is not limited to a rectangular parallelepiped. Figure 1 In the element 1, the first surface 5a and the second surface 5b of the thermoelectric conversion layer 2 are parallel to each other. However, as long as the first surface 5a and the second surface 5b are not in contact with each other, they do not need to be parallel to each other.
[0070] Thermoelectric conversion layer 2 is composed of thermoelectric conversion material A containing Mg. Thermoelectric conversion material A contains at least one element selected from Sb, Bi and Te. In addition, thermoelectric conversion material A contains at least one element selected from Se and Te. Thermoelectric conversion material A has La 2 O 3 type of crystal structure.
[0071] Thermoelectric conversion material A may have a structure represented by formula (I): Mg 3+m A a B b D 2-e E e The element 1 including the thermoelectric conversion layer 2 composed of the n-type thermoelectric conversion material A is an n-type thermoelectric conversion element.
[0072] A in formula (I) is at least one element selected from Ca, Sr, Ba and Yb. B is at least one element selected from Mn and Zn. D is at least one element selected from Sb and Bi. E is at least one element selected from Se and Te. The value of m in formula (I) is in the range of -0.39 to 0.42. The value of a is in the range of 0 to 0.12. The value of b is in the range of 0 to 0.48. The value of e is in the range of 0.001 to 0.06.
[0073] The value of e in formula (I) may be in the range of 0.004 to 0.020. In this case, the thermoelectric conversion performance of the element 1 and the thermoelectric conversion module including the element 1 can be improved.
[0074] m, a and b in formula (I) may satisfy formula (II): m=m'-ab. The value of m' in formula (II) is in the range of 0 or more and 0.21 or less. At least one of the values selected from the value of a and the value of b in formula (II) may be greater than 0 (zero). In this case, the thermoelectric conversion performance of the element 1 and the thermoelectric conversion module having the element 1 can be improved.
[0075] The value of a and the value of b in formula (I) may be 0 (zero). In this case, the thermoelectric conversion performance of element 1 and a thermoelectric conversion module including element 1 can be improved.
[0076] D in formula (I) may be Sb and Bi, and E may be Te. In this case, the thermoelectric conversion performance of the element 1 and the thermoelectric conversion module including the element 1 can be improved.
[0077] Thermoelectric conversion material A may have any composition described in Japanese Patent No. 6127281 or the corresponding U.S. Patent Publication No. 2017 / 0117453 and within the range of formula (I).
[0078] The first electrode 4a is made of a CuZn alloy. The second electrode 4b is made of a CuZn alloy. The composition of the first electrode 4a may be the same as or different from the composition of the second electrode 4b. The composition of the CuZn alloy is expressed, for example, by weight ratio, in the range of Cu:Zn=99:1 to 57:43, or in the range of 68:32 to 63:37. The CuZn alloy may contain, for example, other metal elements other than Cu and Zn in the range of 11 weight % or less. The CuZn alloy may be an alloy classified as brass. Furthermore, as with other common alloys, impurities are allowed to exist in the CuZn alloy.
[0079] The first electrode 4a is bonded to the first surface 5a in a manner covering at least a portion of the first surface 5a. The first electrode 4a may also be bonded to the first surface 5a in a manner covering the entire first surface 5a. The second electrode 4b is bonded to the second surface 5b in a manner covering at least a portion of the second surface 5b. The second electrode 4b may also be bonded to the second surface 5b in a manner covering the entire second surface 5b.
[0080] There is no limitation on the thickness and shape of the first electrode 4 a and the second electrode 4 b .
[0081] The composition of the first intermediate layer 3a is different from the composition of the first electrode 4a and the composition of the thermoelectric conversion layer 2 (i.e., the composition of the thermoelectric conversion material A). The composition of the second intermediate layer 3b is different from the composition of the second electrode 4b and the composition of the thermoelectric conversion layer 2. The composition of the first intermediate layer 3a and the composition of the second intermediate layer 3b may be the same or different.
[0082] The first intermediate layer 3a and the second intermediate layer 3b contain, for example, Cu, Zn and Mg. In this case, the content of Cu is, for example, greater than 50% by weight and less than 70% by weight. The content of Zn is, for example, greater than 25% by weight and less than 35% by weight. The content of Mg is, for example, greater than 0.1% by weight and less than 25% by weight. In the case where the first intermediate layer 3a and the second intermediate layer 3b contain Cu, Zn and Mg, the content of Mg may be less than the content of at least one element selected from Cu and Zn. The first intermediate layer 3a and the second intermediate layer 3b sometimes also contain elements constituting thermoelectric conversion material A (except Mg). In this case, the content of these elements in the first intermediate layer 3a and the second intermediate layer 3b is generally less than the content of Mg. The first intermediate layer 3a and the second intermediate layer 3b may not contain elements constituting thermoelectric conversion material A (except Mg).
[0083] The first intermediate layer 3a is arranged between the first surface 5a and the first electrode 4a in a manner covering at least a portion of the first surface 5a. The first intermediate layer 3a may also be arranged between the first surface 5a and the first electrode 4a in a manner covering the entire first surface 5a. The second intermediate layer 3b is arranged between the second surface 5b and the second electrode 4b in a manner covering at least a portion of the second surface 5b. The second intermediate layer 3b may also be arranged between the second surface 5b and the second electrode 4b in a manner covering the entire second surface 5b.
[0084] The thickness of the first intermediate layer 3a and the second intermediate layer 3b is, for example, 0.1 μm to 300 μm, or 3 μm to 30 μm. The thickness of the first intermediate layer 3a and the thickness of the second intermediate layer 3b may be the same or different.
[0085] The shapes of the first intermediate layer 3 a and the second intermediate layer 3 b are not limited.
[0086] The thermoelectric conversion element of the present disclosure may include at least one selected from other layers and members other than those described above.
[0087] The application of the thermoelectric conversion element of the present disclosure is not limited, and the application is, for example, a thermoelectric conversion module.
[0088] (Manufacturing method)
[0089] An example of the method for producing the thermoelectric conversion element of the present disclosure is shown below. However, the method for producing the thermoelectric conversion element of the present disclosure is not limited to the following example.
[0090] First, a thermoelectric conversion layer 2 composed of a thermoelectric conversion material A is produced. The method for producing the thermoelectric conversion layer 2 is described in, for example, Japanese Patent No. 6127281 or the corresponding U.S. Patent Publication No. 2017 / 0117453.
[0091] Next, a CuZn alloy layer is formed on the first surface 5a and the second surface 5b of the manufactured thermoelectric conversion layer 2. The CuZn alloy layer can be formed, for example, by a spark plasma sintering method (hereinafter referred to as the "SPS method"). However, the method for forming the CuZn alloy layer is not limited to the SPS method. In the process of forming the CuZn alloy layer, a first intermediate layer 3a, a second intermediate layer 3b, a first electrode 4a and a second electrode 4b are formed. It is speculated that the diffusion of Mg from the thermoelectric conversion layer 2 is involved in the formation of these layers and components. If the diffusion of Mg is taken into account, in the process of forming the CuZn alloy layer based on various methods headed by the SPS method, for example, a temperature of about 400 to 800 degrees Celsius is used.
[0092] [Thermoelectric conversion module]
[0093] An example of the thermoelectric conversion module disclosed in the present invention is shown in Figure 2 . Figure 2 Thermoelectric conversion module 11 includes n-type thermoelectric conversion element 1 and p-type thermoelectric conversion element 21 .
[0094] The n-type thermoelectric conversion element 1 includes a first electrode 4a, a second electrode 4b, a first intermediate layer 3a, a second intermediate layer 3b, and a thermoelectric conversion layer 2 as an n-type thermoelectric conversion portion. The n-type thermoelectric conversion portion has a first surface 5a and a second surface 5b. The second surface 5b is a surface on the opposite side of the first surface 5a. The first intermediate layer 3a is provided between the n-type thermoelectric conversion portion and the first electrode 4a. The first intermediate layer 3a is in contact with the n-type thermoelectric conversion portion. The first electrode 4a is in contact with the first intermediate layer 3a. The second intermediate layer 3b is provided between the n-type thermoelectric conversion portion and the second electrode 4b. The second intermediate layer 3b is in contact with the n-type thermoelectric conversion portion. The second electrode 4b is in contact with the second intermediate layer 3b.
[0095] The p-type thermoelectric conversion element 21 includes a third electrode 23a, a fourth electrode 23b, and a p-type thermoelectric conversion portion 22. The p-type thermoelectric conversion portion 22 has a third surface 24a and a fourth surface 24b. The fourth surface 24b is a surface on the opposite side of the third surface 24a. The p-type thermoelectric conversion portion 22 is provided between the third electrode 23a and the fourth electrode 23b. The third electrode 23a and the fourth electrode 23b are in contact with the p-type thermoelectric conversion portion 22.
[0096] One electrode of the n-type thermoelectric conversion element 1 and one electrode of the p-type thermoelectric conversion element 21 are electrically connected to each other. Figure 2In the example of , the first electrode 4a of the n-type thermoelectric conversion element 1 and the third electrode 23a of the p-type thermoelectric conversion element 21 are electrically connected to each other via the first external electrode 13a. A conductive bonding material layer 12a is arranged between the first electrode 4a and the first external electrode 13a. A conductive bonding material layer 12c is arranged between the third electrode 23a and the first external electrode 13a. In addition, the second electrode 4b, which is the other electrode of the n-type thermoelectric conversion element 1, is electrically connected to the second external electrode 13b via the conductive bonding material layer 12b. The fourth electrode 23b, which is the other electrode of the p-type thermoelectric conversion element 21, is electrically connected to the third external electrode 13c via the conductive bonding material layer 12d. In the thermoelectric conversion module 11, electric power can be taken out to the outside via the second external electrode 13b and the third external electrode 13c.
[0097] As the p-type thermoelectric conversion element 21 , a known element can be used.
[0098] The structure of the bonding material layers 12a, 12b, 12c, and 12d is not limited as long as they have conductivity.
[0099] As the first external electrode 13 a , the second external electrode 13 b , and the third external electrode 13 c , known external electrodes can be used.
[0100] Thermoelectric conversion module 11 can be manufactured by a known method.
[0101] The application of the thermoelectric conversion module of the present disclosure is not limited. The thermoelectric conversion module of the present disclosure can be used for various applications including the applications of conventional thermoelectric conversion modules.
[0102] Example
[0103] Hereinafter, the thermoelectric conversion element of the present disclosure will be described in more detail with reference to examples. The thermoelectric conversion element of the present disclosure is not limited to the various modes shown in the following examples.
[0104] (Example 1)
[0105] (Production of Sintered Body)
[0106] A sintered body composed of the thermoelectric conversion material A was produced as follows. The composition of the thermoelectric conversion material A was Mg 3.08 Sb 1.49 Bi 0.49 Te 0.02 .
[0107] First, granular antimony (5.48 g, 0.045 mol) and granular bismuth (3.01 g, 0.0144 mol) were melted at a temperature ranging from 1000 to 1500 degrees Celsius by arc melting. Thus, an alloy of antimony (Sb) and bismuth (Bi) was obtained. Then, the obtained alloy was pulverized in a mortar to form a powder of SbBi.
[0108] Next, magnesium powder (2.33 g, 0.096 mol) and tellurium powder (0.0474 g, 0.0006 mol) were added to the SbBi powder. Then, these powders were thoroughly mixed. The molar ratio of Mg, Sb, Bi and Te as starting materials was Mg:Sb:Bi:Te=0.096:0.045:0.0144:0.0006, i.e. 3.20:1.50:0.48:0.02.
[0109] Next, the mixed powder is fed to a tablet press to form tablets. The tablets are then placed in a carbon crucible. The carbon crucible is filled with argon gas. The tablets are then heated at a temperature in the range of 800 to 1000 degrees Celsius for 10 seconds. The tablets are melted by heating to form ingots.
[0110] Next, the ingot was placed in a mortar placed in a glove box filled with argon gas. The ingot was crushed in the mortar to form a powder of MgSbBiTe. The particle size of the formed powder was 100 μm or less.
[0111] Then, the MgSbBiTe powder is sintered by the SPS method to form a sintered body. The sintering performed by the SPS method is implemented as follows. First, the MgSbBiTe powder is filled into a cylindrical mold (i.e., a sintering mold) made of graphite. The mold has an outer shape of 50 mm and an inner diameter of 10 mm. The filling is implemented in a glove box filled with argon. Then, the mold is contained in the chamber of a spark plasma sintering device. The chamber is controlled to be an argon atmosphere. Then, a pressure of 50 MPa is applied to the powder filled in the mold, and a pulse current is applied to the mold by the sintering device. By applying the current, a heating rate of 20 degrees Celsius / minute is achieved. After the temperature of the mold reaches 600 degrees Celsius as the sintering temperature, the temperature is maintained for 30 minutes. Then, the heating of the mold is stopped by stopping the current. After the temperature of the mold is reduced to room temperature, the cylindrical sintered body is taken out from the mold.
[0112] The evaluation based on X-ray diffraction measurement confirmed that the thermoelectric conversion material A constituting the sintered body had La 2 O 3 The X-ray diffraction pattern of the thermoelectric conversion material A obtained by X-ray diffraction measurement is shown in Figure 3 In addition, CuKα rays were used for X-ray diffraction measurement.
[0113] The composition of the thermoelectric conversion material A constituting the sintered body was confirmed to be Mg 3.08 Sb 1.49 Bi 0.49 Te 0.02 The EDX spectrum of thermoelectric conversion material A is shown in Figure 4 For EDX, an energy dispersive X-ray spectrometer for SEM (manufactured by Bruker, XFlash6|10) was used. For SEM combined with the above-mentioned spectrometer, a field emission SEM (FE-SEM; manufactured by Hitachi High-Technologies Corporation, SU8220) was used.
[0114] (Formation of CuZn Alloy Layer)
[0115] The upper and lower surfaces of the cylindrical sintered body were ground with #400 sandpaper. The grinding was performed in a glove box filled with argon gas. The height of the ground sintered body was 3.5 mm.
[0116] Next, CuZn alloy layers were formed on the upper surface (first surface) and the lower surface (second surface) of the sintered body by SPS method. The formation of the CuZn alloy layer by SPS method was carried out as follows.
[0117] First, the ground sintered body is placed in a cylindrical mold used for making sintered bodies. Then, while the mold is standing up, 0.336 g of CuZn powder is filled into the mold from the top. The CuZn powder is deposited on the first surface of the sintered body contained in the mold. Then, the deposited CuZn powder is gently pressed. Then, the mold is slowly turned over to swap the upper and lower surfaces of the mold. Then, while the mold is standing up, 0.336 g of CuZn powder is filled into the mold from the swapped top. The CuZn powder is deposited on the second surface of the sintered body contained in the mold. Then, the deposited CuZn powder is gently pressed. The composition of the alloy constituting the CuZn powder is Cu:Zn=65:35 (weight ratio). The sintered body is placed in the mold and the CuZn powder is filled into the mold in a glove box filled with argon gas.
[0118] Then, the mold is housed in the chamber of the spark plasma sintering device. The chamber is controlled to be an argon atmosphere. Next, a pressure of 90 MPa is applied to the sintered body and CuZn powder filled in the mold, and a pulse current is applied to the mold by the sintering device. By applying the current, a heating rate of 60 degrees Celsius per minute is achieved. After the temperature of the mold reaches 600 degrees Celsius as the sintering temperature, the temperature is maintained for 15 minutes. Then, the heating of the mold is stopped by stopping the current. After the temperature of the mold is reduced to room temperature, a cylindrical sintered body having a CuZn alloy layer on the upper and lower surfaces is taken out from the mold.
[0119] Next, the surface of the CuZn alloy layer of the taken-out sintered body was ground using #400 sandpaper. The grinding was performed in a glove box filled with argon gas. The height of the ground sintered body was 4.0 mm. Then, the ground sintered body was cut using a cutter to form a rectangular thermoelectric conversion element having a width of 3.5 mm, a depth of 3.5 mm, and a height of 4.0 mm.
[0120] The state of the portion located near the interface between the sintered body and the CuZn alloy layer in the cut surface of the formed thermoelectric conversion element was evaluated by SEM. In addition, the composition of the portion located near the interface between the sintered body and the CuZn alloy layer was evaluated by using EDX to analyze the cut surface. The image of the portion located near the interface in the cut surface observed by SEM is shown in FIG. Figure 5A The results of EDX analysis of the above parts are shown in Figure 5B . EDX is used for ray analysis along the Figure 5A The line segment OX of the observed image shown is implemented. Figure 5B The change in composition depending on the distance from the point O of the line segment OX is shown in FIG. The above-mentioned apparatus was used for SEM and EDX.
[0121] like Figure 5A and Figure 5B As shown in FIG. 1 , two boundaries M1 and M2 where the composition greatly changes are observed near the interface between the sintered body and the CuZn alloy layer. The portion between point O and boundary M1 is composed of Cu and Zn, that is, the CuZn alloy layer that functions as the electrode 4. The portion between boundary M2 and point X is composed of Mg, Sb, Bi, and Te, that is, the thermoelectric conversion layer 2 that functions as the thermoelectric conversion unit. Furthermore, due to the low content, Figure 5B The figure corresponding to Te is not clearly shown in the figure. On the other hand, the portion between the boundary M1 and the boundary M2 is a layer composed of Cu, Zn and Mg and having a composition different from that of the electrode 4 and the sintered body 2. That is, the formation of the intermediate layer 3 containing Cu, Zn and Mg is confirmed between the electrode 4 and the thermoelectric conversion layer 2. Figure 5AAs shown, the electrode 4, the intermediate layer 3 and the thermoelectric conversion layer 2 are all dense layers.
[0122] Next, the resistance value between a pair of CuZn alloy layers in the formed thermoelectric conversion element was measured by a four-terminal method. The measurement was performed using a Keithley 2400 Source Meter manufactured by Dongyang Audio-Technica Co., Ltd. The measured resistance value was 16.4 mΩ. In addition, the resistivity p calculated from the measured resistance value by the following formula was 50.2 μΩ·m.
[0123] ρ=R×A / L
[0124] In the above formula, R is the resistance value between the CuZn alloy layers, A is the cross-sectional area of the thermoelectric conversion element (3.5 mm×3.5 mm), and L is the height of the thermoelectric conversion element (4.0 mm).
[0125] (Example 2)
[0126] The thermoelectric conversion element was produced in the same manner as in Example 1 except that the sintering temperature for forming the sintered body was changed to 500 degrees Celsius and the sintering time was changed to 15 minutes. The evaluation based on X-ray diffraction measurement confirmed that the thermoelectric conversion material A constituting the sintered body had La 2 O 3 In addition, through the evaluation based on EDX, it was confirmed that the composition of the thermoelectric conversion material A constituting the sintered body was the same as that of Example 1. 3.08 Sb 1.49 Bi 0.49 Te 0.02 .
[0127] As in Example 1, the state of the portion located near the interface between the sintered body and the CuZn alloy layer in the cut surface of the formed thermoelectric conversion element was evaluated by SEM. In addition, the composition of the portion located near the interface between the sintered body and the CuZn alloy layer was evaluated by EDX radiographic analysis of the cut surface. The image of the portion located near the interface in the cut surface observed by SEM is shown in FIG. Fig. 6A The results of EDX analysis of the above parts are shown in Figure 6B . EDX is used for ray analysis along the Fig. 6A The line segment OX of the observed image shown is implemented. Figure 6B , the change in composition based on the distance from point O of line segment OX is shown.
[0128] like Fig. 6A and Figure 6BAs shown in FIG. 1 , two boundaries M1 and M2 with greatly changed compositions are observed near the interface between the sintered body and the CuZn alloy layer. The portion between point O and boundary M1 is composed of Cu and Zn, that is, the CuZn alloy layer that functions as the electrode 4. The portion between boundary M2 and point X is composed of Mg, Sb, Bi, and Te, that is, the thermoelectric conversion layer 2 that functions as the thermoelectric conversion unit. Furthermore, due to the low content, Figure 6B The figure corresponding to Te is not clearly shown in the figure. On the other hand, the portion between the boundary M1 and the boundary M2 is a layer composed of Cu, Zn and Mg and having a composition different from that of the electrode 4 and the sintered body 2. That is, the formation of the intermediate layer 3 containing Cu, Zn and Mg is confirmed between the electrode 4 and the thermoelectric conversion layer 2. Fig. 6A As shown, the electrode 4, the intermediate layer 3 and the thermoelectric conversion layer 2 are all dense layers.
[0129] Next, the resistance value between the pair of CuZn alloy layers and the resistivity ρ in the thermoelectric conversion element formed were evaluated in the same manner as in Example 1. The measured resistance value was 7.05 mΩ. The resistivity ρ was 21.6 μΩ·m.
[0130] (Comparative Example 1)
[0131] The upper and lower surfaces of the cylindrical sintered body made in the same manner as in Example 1 were ground using #400 sandpaper. The grinding was carried out in the atmosphere. The height of the ground sintered body was 0.7 mm. Then, Ni layers were formed on the upper surface (first surface) and lower surface (second surface) of the sintered body by electrolytic plating. The thickness of each Ni layer formed was about 5 μm. Next, the sintered body having the Ni layer was cut using a cutter to form a rectangular thermoelectric conversion element having dimensions of 1.0 mm in width, 1.0 mm in depth, and 0.71 mm in height.
[0132] The state of the portion located near the interface between the sintered body and the Ni layer in the cut surface of the formed thermoelectric conversion element was evaluated by SEM. In addition, the composition of the portion located near the interface between the sintered body and the Ni layer was evaluated by using EDX to analyze the cut surface. The image of the portion located near the interface in the cut surface observed by SEM is shown in FIG. Fig. 7A The results of EDX analysis of the above parts are shown in Figure 7B . EDX is used for ray analysis along the Fig. 7A The line segment OX of the observed image shown is implemented. Figure 7B , the change in composition based on the distance from point O of line segment OX is shown.
[0133] like Fig. 7A and Figure 7BAs shown in FIG. 1 , two boundaries M1 and M2 with greatly changed compositions are observed near the interface between the sintered body and the Ni layer. The portion between point O and boundary M1 is composed of Ni, i.e., the Ni layer that functions as the electrode 53. The portion between boundary M2 and point X is composed of Mg, Sb, Bi, and Te, i.e., the thermoelectric conversion layer 51 that functions as the thermoelectric conversion unit. Furthermore, due to the low content, Figure 7B The graph corresponding to Te is not clearly shown in the figure. On the other hand, the portion between the boundary M1 and the boundary M2 is a modified layer 52 which is composed of Mg, Sb, Bi, and Te like the thermoelectric conversion layer 51, but has a composition completely different from that of the thermoelectric conversion layer 51. More specifically, the content of Mg in the modified layer 52 is sharply reduced compared to that in the thermoelectric conversion layer 51. In addition, as Fig. 7A As shown, a plurality of pores are observed in the altered layer 52. Judging from the composition and the formation of the pores, it is presumed that the altered layer 52 is formed due to the diffusion and outflow of Mg from the thermoelectric conversion layer 51 near the interface.
[0134] Next, the resistance value and resistivity ρ between a pair of Ni layers in the formed thermoelectric conversion element were measured in the same manner as in Example 1. In the calculation of resistivity ρ, R in the above formula is the resistance value between the Ni layers, A is the cross-sectional area of the thermoelectric conversion element (1.0 mm × 1.0 mm), and L is the height of the thermoelectric conversion element (0.71 mm). The measured resistance value is 841 mΩ. In addition, the resistivity ρ was found to be 1185 μΩ·m.
[0135] The resistance values between the electrodes and the resistivity ρ in the thermoelectric conversion elements of Examples 1 and 2 and Comparative Example 1 are summarized in Table 1 below.
[0136] Table 1
[0137] Resistance value (mΩ) Resistivity (μΩ·m) Example 1 16.4 50.2 Example 2 7.05 21.6 Comparative Example 1 841 1185
[0138] As shown in Table 1, in the thermoelectric conversion elements of Examples 1 and 2, the resistance is significantly lower than that of the thermoelectric conversion element of Comparative Example 1.
[0139] Industrial Availability
[0140] The thermoelectric conversion element disclosed in the present invention can be used for various applications including applications of conventional thermoelectric conversion elements.
Claims
1. A thermoelectric conversion element, characterized in that: comprising a first electrode, a second electrode, a first intermediate layer, a second intermediate layer and a thermoelectric conversion layer, The first intermediate layer is provided between the thermoelectric conversion layer and the first electrode. The first intermediate layer is in contact with the thermoelectric conversion layer, The first electrode is in contact with the first intermediate layer, The second intermediate layer is provided between the thermoelectric conversion layer and the second electrode. The second intermediate layer is in contact with the thermoelectric conversion layer, The second electrode is in contact with the second intermediate layer, The first electrode and the second electrode are made of CuZn alloy. The thermoelectric conversion layer is composed of a thermoelectric conversion material containing Mg. The thermoelectric conversion material contains at least one element selected from Sb and Bi, The thermoelectric conversion material contains at least one element selected from Se and Te, The thermoelectric conversion material has a La2O3 type crystal structure, The composition of the first intermediate layer is different from the composition of the first electrode and the composition of the thermoelectric conversion layer. The composition of the second intermediate layer is different from the composition of the second electrode and the composition of the thermoelectric conversion layer. The first intermediate layer and the second intermediate layer contain Cu, Mg and at least one element selected from Sb and Bi, The thermoelectric conversion layer, the first intermediate layer and the first electrode are continuous, The thermoelectric conversion layer, the second intermediate layer and the second electrode are continuous, Mg exists continuously in the thermoelectric conversion layer and the first intermediate layer, Mg exists continuously in the thermoelectric conversion layer and the second intermediate layer, The content of Cu in the first intermediate layer is 50% by weight or more and 70% by weight or less, The content of Cu in the second intermediate layer is 50% by weight or more and 70% by weight or less, The content rate of Mg in the first intermediate layer is lower than the content rate of Cu, The content rate of Mg in the second intermediate layer is lower than the content rate of Cu.
2. The thermoelectric conversion element according to claim 1, characterized in that The thermoelectric conversion material has the formula (I): Mg 3+m A a B b D 2-e E e Represents the composition, and is n-type, In the formula (I), A is at least one element selected from Ca, Sr, Ba and Yb, B is at least one element selected from Mn and Zn, D is at least one element selected from Sb and Bi, E is at least one element selected from Se and Te, The value of m in the formula (I) is in the range of -0.39 to 0.42, The value of a is in the range of 0 to 0.
12. The value of b is in the range of 0 to 0.
48. The value of e is in the range of 0.001 to 0.
06.
3. The thermoelectric conversion element according to claim 2, characterized in that The value of e in the formula (I) is in the range of 0.004 to 0.
020.
4. The thermoelectric conversion element according to claim 2 or 3, characterized in that: m, a and b of formula (I) satisfy formula (II): m=m'-ab, The value of m' in the formula (II) is in the range of 0 to 0.21, At least one value selected from the value of a and the value of b is greater than 0.
5. The thermoelectric conversion element according to claim 2 or 3, characterized in that: The value of a and the value of b in the formula (I) are 0.
6. The thermoelectric conversion element according to claim 2 or 3, characterized in that: In the formula (I), D is Sb and Bi, E is for Te.
7. A thermoelectric conversion module, characterized in that: It has an n-type thermoelectric conversion element and a p-type thermoelectric conversion element, The n-type thermoelectric conversion element includes a first electrode, a second electrode, a first intermediate layer, a second intermediate layer, and an n-type thermoelectric conversion portion. The first intermediate layer is provided between the n-type thermoelectric conversion portion and the first electrode. The first intermediate layer is in contact with the n-type thermoelectric conversion portion, The first electrode is in contact with the first intermediate layer, The second intermediate layer is provided between the n-type thermoelectric conversion portion and the second electrode. The second intermediate layer is in contact with the n-type thermoelectric conversion portion, The second electrode is in contact with the second intermediate layer, The p-type thermoelectric conversion element includes a third electrode, a fourth electrode, and a p-type thermoelectric conversion portion. The p-type thermoelectric conversion unit is provided between the third electrode and the fourth electrode. The third electrode and the fourth electrode are in contact with the p-type thermoelectric conversion unit. The first electrode or the second electrode in the n-type thermoelectric conversion element is electrically connected to the third electrode or the fourth electrode in the p-type thermoelectric conversion element. The n-type thermoelectric conversion element is the thermoelectric conversion element according to any one of claims 1 to 6.
Citation Information
Patent Citations
Guide apparatus for switching door in garbage wagon
JP1986027281B2
Thermoelectric conversion element, thermoelectric conversion element module, and method of manufacturing the same
US20130199593A1
Thermoelectric conversion module
US20140216515A1
Thermoelectric conversion material
US20170117453A1